The role of leaders in shaping school culture - Plaku, Anila Koli; Leka, Klodiana (Frontiers in Education, 2025)
Principals plays a decisive role in shaping school culture. First, based on teachers’ perceptions, this research explores indicators that differentiate schools with a positive culture from those with a negative culture. Second, it investigates potential perceptual differences between teachers and principals regarding school culture. The research approach is a grounded theory, utilizing unstructured interviews with principals, semi-structured interviews with school teachers, and observations conducted over a two-month period. The study population includes teachers and principals from eight secondary schools. From this population, the study sample consists of 12 principals and 137 teachers. The study findings evidenced that schools with a positive culture stand out for fostering a culture of cooperation among staff, celebrating school achievements, and collaborating in groups to develop curricular plans and programs. Furthermore, schools with a positive culture maintain strong connections with the community through participation in local ceremonies and adherence to community customs. The study concludes that the actions taken by leaders are closely associated with changes in school culture over time. Schools characterized by a positive culture cultivate a benevolent and productive environment, fostering satisfaction among staff. In contrast, schools with a negative culture often exhibit manifestations such as indifference, fragmentation, interpersonal conflicts, and a lack of job satisfaction.